Elaboração e implementação de um roteiro de visita “Cerrado na UFSCar – Parque Ecológico de São Carlos” com abordagem integrada da conservação da fauna - Mello, Amanda Carolina de (Universidade Federal de São Carlos, 2019)
The Cerrado, synonym of resistance and resilience, is losing abruptly space in our society where economic interests “speaks louder”. Even knowing of their enormous biodiversity, of endemic species, importance in relation to the maintenance of water, is not enough to conserver this domain, that has been devastated by human activities such as agriculture and livestock. The existence of a Cerrado area inside a university and having as a neighbour the illustrious Parque Ecológico de São Carlos (PESC), a zoo focused on Brazilian and South American fauna, makes this research promotes the visibility of spaces with enormous potential for visitation and scientific research. Based on the problematic and importance of developing this project, the proposed objectives were the elaboration and implementation, in a participatory way, of a monitored visit roadmappassing through an area of Cerrado at the university and the Parque Ecológico de São Carlos, promoting reflections about the in situ and ex situ conservation. The methodology used was a qualitative approach, based on critical ambiental education and the systematization of experiences, that promoted the effective participation of those involved, as well as reflection and critical interpretation on all the processes and elements present in the experience. The investigation occurred in four moments: Moment I: an initial diagnostic was made to identify reasons why people go to the Cerrado and the PESC, as well as previous knowledge about the Cerrado and zoos. Moment II: interviews and a participative workshop was made with monitors were held to define the themes to be addressed and the route of the roadmap. Moment III: elaboration of the roadmap based on data previously collected and definition of the best route after two pilot visits. Moment IV: disclosure of three visits to this new roadmap. In the visits to the Cerrado-PESC we applied pre and post-visit questionnaires to understand the profile of the visiting public, their expectations, previous knowledge about the Cerrado, zoos and conservation, as well as suggestions and criticism of the activities performed. In Moment I, 162 questionnaires were collected, which revealed great curiosity of people to know the Cerrado and knowing more about it, the visiting public of PESC comes to him for leisure, family outing; the answers obtained helped in the reflection of the activities and elaboration of the roadmap. In Moment II interviews were obtained with seven monitors, identifying previous knowledge about the Cerrado, zoos and the possibility of a roadmap integrating the two spaces and a participatory workshop to build a roadmap proposal. Moment III: there were two pilot visits to define the best route and topics addressed and, finally in the Moment IV visits were made by the Cerrado-PESC roadmap, with the participation of 41 people, who demonstrated through the questionnaire, the contentment regarding the visit, to the topics addressed. The moments, experiences were very important and the elaborated roadmap can and should be modified in relation to the themes, the way itself, promoting visits to diverse publics, because it is essential that reflections and improvements of practice occur. We hope that the research carried out could contribute to a better understanding of integrated conservation and the appreciation of both environments by its visitors.
Preparation and implementation of a visit roadmap "Cerrado at UFSCar - Parque Ecológico de São Carlos" with integrated approach to wildlife conservation
Preparación e implementación de un guión de visita "Cerrado en UFSCar - Parque Ecológico de São Carlos" con enfoque integrado para la conservación de la vida silvestre
Keywords: Conservação da fauna; Sistematização de experiências; Trilha interpretativa; Educação Ambiental; Zoológicos; Wildlife conservation; Systematization of experiences; Interpretive trail; Environmental education; Zoos; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS